Hypovitaminosis D in patients with oral leukoplakia: insights from a cross-sectional study - Maturana-Ramirez, Andrea; Aitken-Saavedra, Juan; Mora-Ferraro, Dante; Rojas-Zúñiga, Gabriel; Espinoza-Santander, Iris; Rojas-Alcayaga, Gonzalo; Ortega-Pinto, Ana; Reyes, Montserrat; Lazo, Diego; Caamanão, Egardo (Frontiers in Oncology, 2025)
IntroductionOral leukoplakia is one of the most frequent oral potentially malignant disorders. The present study aims to compare serum vitamin D levels between patients with and without oral leukoplakia, by smoking habit.MethodsThis cross-sectional study involved a group of 45 cases with oral leukoplakia and a control group with 45 individuals. In both groups a pathology report was done, and for leukoplakia a binary classification of low- and high-grade epithelial dysplasia was employed. Serum 25(OH)D3 vitamin D levels, and data on smoking status, age, gender, comorbidities, and clinical and pathological characteristics were collected for both groups.Resultsvitamin D levels were lower in the oral leukoplakia group with a median of 19.1 ng/ml, while the control group had a median of 24.8 ng/ml. When subdividing each group by smoking habit, the smoking case group had a median of 19.4 ng/ml (IQR: 15.7-21.5 ng/ml), the non-smoking case group had 18.8 ng/ml (IQR: 13.6-29.2 ng/ml), the smoking control group had 21.8 ng/ml (IQR: 17.5-27.3 ng/ml), and the non-smoking control group had 25.4 ng/ml (IQR: 20.4-32.9 ng/ml) (p<0.05). When comparing serum vitamin D levels, statistically significant differences were found between the smoking case group versus the non-smoking control group and between the non-smoking case group versus the non-smoking control group (p<0.05). Serum vitamin D levels by histopathological diagnosis showed no differences between leukoplakia groups.DiscussionThis study shows that serum vitamin D levels were lower in patients with OL compared to those without OL, which was more evident in the smoking group. Patients with OL were previously observed to have hypovitaminosis D, without assessing smoking habits. This finding suggests a possible role of vitamin D deficiency in the development of OL, which could be more marked in smokers. This opens the possibility of future research on vitamin D as a chemopreventive agent in the malignant transformation of OL, and to evaluate the relationship between smoking and hypovitaminosis D.